Penatalaksanaan liken amiloidosis dengan desoksimetason dan asam salisilat topikal: laporan kasus - Harry Gunawan; Flora Anisah Rakhmawati (DiscoverSys Inc., 2021)
Background: Cutaneous amyloidosis is characterized by the deposition of amyloid material in the dermis or epidermis, usually limited to the dermal papillae in local cutaneous amyloidosis. Dermal involvement could lead to skin thickening with a waxy surface. The prevalence of cutaneous amyloidosis is relatively rare, only 0.2 – 0.3 % and is more common in individuals with darker skin phototype. The aim of this study is to report a case of lichen amyloidosis associated with its treatment using a combination of desoxymethasone and salicylic acid.Case Report: We report a 27-year-old woman who came with multiple hyperpigmented papules, which were based on sharp-bordered brown macules with scales and lichenification that felt very itchy on both of her lower legs since 5 years ago. The same lesions also appeared on both her arms 2 years ago. She had skin phototype IV. She denied any history of chronic friction in those areas. On histopathological examination with hematoxylin and eosin (H&E) staining, amorphous deposits were found in the papillae dermis surrounded by melanophages. The patient was treated with topical therapy of 0.25% desoximetasone and 3% salicylic acid and was educated to avoid friction on the lesions. The patient admitted that the itchiness was reduced, but the lesion did not improve.Result: Based on the patient’s age and sex, she belonged to a less common group affected by lichen amyloidosis. Phototype skin IV was the risk factor identified in this case. She denied any history of chronic friction on her skin. Lichen amyloidosis was diagnosed based on a typical lesion found at the predilection sites and was confirmed with histopathological examination with H&E staining. Topical desoximetasone and salicylic acid didn’t result in clinical improvement.Conclusion: The diagnosis of lichen amyloidosis was confirmed with histopathological examination. H&E staining could demonstrate amyloid deposit clearly. Treatment of cutaneous amyloidosis is generally unsatisfactory and may require a combination of therapeutic modalities. Latar Belakang: Amiloidosis kutaneus merupakan deposisi material amiloid pada lapisan dermis atau epidermis, umumnya terbatas hingga papilla dermis pada kasus amiloidosis kutaneus lokal. Keterlibatan dermis dapat menyebabkan penebalan kulit dengan permukaan seperti lilin. Prevalensi amiloidosis kutaneus relatif jarang yaitu hanya 0,2-0,3 % dan lebih sering terjadi pada individu dengan fototipe kulit lebih gelap. Tujuan penelitian ini untuk melaporkan kasus liken amiloidosis terkait dalam penatalaksanaannya menggunakan kombinasi desoksimetason dan asam salisilat. Laporan Kasus: Dilaporkan pasien perempuan berusia 27 tahun memiliki papul multipel dengan hiperpigmentasi, dasar kulit makula kecoklatan berbatas tegas disertai skuama dan likenifikasi yang terasa sangat gatal pada area kedua tungkai bawah sejak 5 tahun yang lalu. Lesi yang sama juga muncul pada kedua lengan sejak 2 tahun yang lalu. Pasien memiliki fototipe kulit IV. Pasien menyangkal riwayat gesekan kronis pada area tersebut. Pada pemeriksaan histopatologis dengan pewarnaan hematoxylin dan eosin (H&E), didapatkan deposit amorf di dalam papilla dermis dikelilingi melanofag. Pasien mendapatkan terapi krim topikal desoksimetason 0,25 % dan asam salisilat 3 %, serta diedukasi untuk menghindari gesekan pada lesi. Pasien mengaku gatal berkurang, namun tidak didapatkan perbaikan pada lesi.Hasil: Berdasarkan usia dan jenis kelamin, pasien termasuk kelompok yang jarang terjadi liken amiloidosis. Kulit pasien tergolong dalam fototipe IV merupakan faktor risiko pada pasien. Pasien menyangkal adanya riwayat gesekan kronis. Diagnosis liken amyloidosis didasarkan lesi yang khas dengan lokasi sesuai predileksi dan diagnosis ditegakkan melalui pemeriksaan histopatologis dengan pewarnaan H&E. Terapi desoksimetason dan asam salisilat topikal tidak menunjukkan perbaikan secara klinis.Kesimpulan: Pewarnaan H&E dapat mendemonstrasikan deposit amiloid dengan baik. Terapi amiloidosis kutaneus umumnya tidak memuaskan dan mungkin membutuhkan kombinasi berbagai modalitas terapi.